2021
DOI: 10.1007/jhep01(2021)043
|View full text |Cite
|
Sign up to set email alerts
|

Mimetic gravity in (2 + 1)-dimensions

Abstract: One of the most important achievements in general relativity has been discovery of the (2 + 1)-dimensional black hole solutions of Einstein gravity in anti-de Sitter (AdS) spacetime [7]. In this paper, we construct, for the first time, the (2 + 1)-dimensional solutions of mimetic theory of gravity. These solutions may provide a powerful background to investigate the physical properties of mimetic gravity and examine its viability in lower spacetime dimensions. In particular, some physical properties of station… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 67 publications
2
7
0
Order By: Relevance
“…In the present work, we are going to find the charged static and rotating solutions in the context of mimetic gravity in D > 4 space-time dimensions and investigate their physical properties. The solutions are indeed the generalizations of those obtained in [20,21] to higher dimensions. Depending on their identifications, one can interpret them as black holes, or black strings/branes.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…In the present work, we are going to find the charged static and rotating solutions in the context of mimetic gravity in D > 4 space-time dimensions and investigate their physical properties. The solutions are indeed the generalizations of those obtained in [20,21] to higher dimensions. Depending on their identifications, one can interpret them as black holes, or black strings/branes.…”
Section: Introductionsupporting
confidence: 68%
“…It also was shown that, in the framework of mimetic gravity, a schwarzschild black hole can be exist without singularity [18]. Recently, in [19][20][21] the authors obtained topological black hole, black string as well as 3-dimensional BTZ-like solutions in the framework of mimetic gravity. From the cosmological point of view, in [22] the authors indicate that the singularities in cosmological solutions can be easily removed by considering the longitudinal degree of freedom of gravity to be dynamical.…”
Section: Introductionmentioning
confidence: 99%
“…The BH solutions of gravitational theory are considered as the most interesting astrophysical objects that exist in physics. These amazing configurations supply us with a strong indication for discovering several branches of physics, e.g., thermodynamics, information theory, paramagnetism-ferromagnetism phase transition, holographic hypothesis, superconducting phase transition, condensed matter physics, quantum gravity, superfluids, and spectroscopy [52]. Recently, BH solutions have gained much attention after several efforts to understand the confusion of the information paradox [53] and the shadow of supermassive BHs as the first results of the M87 Event Horizon Telescope [54].…”
Section: Introductionmentioning
confidence: 99%
“…The existence of soft gravitons and/or soft photons, on the BH horizon and their quantum state information which is stored on a holographic plate at the future boundary of the horizon, are discussed in [1]. The entropy and microscopic construction of BH near the horizon are discussed through the soft hairs in [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%